Development of Android Education Application for Arabic Alphabet with Artificial Intelligence for Children - Pamungkas, Brian Aji; Dharmawan, Alexander; Yusup, Yusup (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Seventy-two percent of the Muslim population in Indonesia is illiterate in Arabic script, thus requiring early childhood education. Young children often struggle to directly learn Arabic script, necessitating the role of instructors. However, most instructors in madrasahs do not teach Arabic script intensively, prompting the need for interactive and engaging learning media for children. Therefore, the development of an Android application for teaching Arabic script to young children is crucial. By employing the Rapid Application Development (RAD) method, an Android application can be developed, incorporating gamification for interactive learning and the AI Life Cycle for developing a 3D Arabic script object detection model useful for automatic correction systems. The AI model is developed using SSD MobileNet v2 FPN Lite 640x640. Sixteen trials are conducted for separate letter modeling and two for connected letters. The separate letter modeling yields the best result in the 8th trial with a total loss of 0.182882 out of 1, using parameters of 16 batch size, 30,000 num steps, and checkpoint from the 7th trial. Connected letter modeling yields the best result in the 2nd trial with parameters of 8 batch size, 14,000 num steps, and checkpoint from the 1st trial. The output is an offline Android application integrating gamification and AI technology, featuring two categories of questions, each with 20 items.